ASSOCIATION BETWEEN POLYMORPHIC MARKERS OF THE IL4 (с-590Т) AND IL10 (с-597А) GENES AND PSORIATIC ARTHRITIS - M. V. Smolnikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Psoriatic arthritis is a chronic progressive disease of joints developing along with psoriasis. Likewise arthritis and psoriasis alone, it represents the systemic multifactorial disease of unknown etiology; therefore prevention of the disease is inefficient. Genetic predisposition to psoriatic arthritis development is proposed with essential role of genes coding for cytokines, the main mediators of immune response. A study of the prevalence of polymorphisms of the genes of anti-inflammatory cytokines IL4 (C-590T) and IL10 (C-597A) in patients with psoriasis, psoriatic arthritis and healthy donors was carried out. The prevalence of the polymorphisms in the European population of Krasnoyarsk was obtained. An association of the C-590T polymorphic marker of the promoter region of the IL4 gene with psoriatic arthritis was established. The obtained results suggest that the C-590 allele is a contributing factor to heavier course of psoriasis and the development of bone system pathology.